2013
DOI: 10.1007/s12088-013-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol and Plant Growth Promotion Characterization of Bacillus Species Isolated from Calendula officinalis Rhizosphere

Abstract: The phenotypic and genotypic diversity of the plant growth promoting Bacillus genus have been widely investigated in the rhizosphere of various agricultural crops. However, to our knowledge this is the first report on the Bacillus species isolated from the rhizosphere of Calendula officinalis. 15 % of the isolated bacteria were screened for their important antifungal activity against Fusarium oxysporum, Botrytis cinerea, Aspergillus niger, Cladosporium cucumerinium and Alternaria alternata. The bacteria identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…2), probably due to the formation of spores (Additional file 1: Figure S1). A similar behaviour was reported for other Bacillus species (Bharucha et al 2013; Ait Kaki et al 2013; Santos et al 2014).…”
Section: Resultssupporting
confidence: 84%
“…2), probably due to the formation of spores (Additional file 1: Figure S1). A similar behaviour was reported for other Bacillus species (Bharucha et al 2013; Ait Kaki et al 2013; Santos et al 2014).…”
Section: Resultssupporting
confidence: 84%
“…Paenibacillus isolated from the rhizosphere of Calendula sp. has been reported to possess biocontrol and plant growth promotion potential (Ryu et al 2005 ; Kaki et al 2013 ). B. safensis strain TS22 and B. humi strain TS9 were found to be postive for cellulase, siderophore as well as IAA production.…”
Section: Resultsmentioning
confidence: 99%
“…The production of IAA by rhizobacteria is so important in supporting plant growth and development by interfering with the endogenous IAA produced by the plant and serve in defense responses [2729]. Studies showed that Bacillus amyloliquefaciens is known to produce a substantial amount of IAA [17, 30]. Another important trait displayed by Bacillus species (BT42) is the ability to produce an enzyme ACC deaminase.…”
Section: Discussionmentioning
confidence: 99%